COVID-19 prevention behaviour is differentially motivated by primary psychopathy, grandiose narcissism and vulnerable Dark Triad traits. (April 2023) - Blanchard, Alyson E.; Keenan, Greg; Heym, Nadja; Sumich, Alex
Abstract: Dark Triad traits (psychopathy, narcissism) are associated with nonadherence to COVID-19 prevention measures such as social distancing and wearing face masks, although the psychological mechanisms underpinning this relationship remain unclear. In contrast, high threat-sensitivity may motivate compliance, and maybe seen in relation to vulnerable dark traits (secondary psychopathy, vulnerable narcissism and borderline personality disorder). The relationship between vulnerable dark traits and COVID-19 prevention behaviour has not been examined. During April 2021, participants ( n  = 263) completed an online psychometric study assessing engagement with COVID-19 prevention behaviour, traditional DT traits (primary psychopathy; grandiose narcissism) and vulnerable DT traits. Potential indirect effects were fear of COVID-19, perceived coronavirus severity, belief in COVID-19 conspiracy theories and altruism. Model of path analysis identified predictors of engagement in disease prevention behaviour. Primary psychopathy, grandiose narcissism, secondary psychopathy and BPD were associated with less COVID-19 prevention behaviour, with an indirect effect of reduced coronavirus severity. Grandiose narcissism and BPD were also motivated by COVID-19 conspiracy theories, and increased prevention behaviour when fear of COVID-19 was higher. No direct or indirect effects were observed for vulnerable narcissism. The current study is the first to elucidate psychological mechanisms linking vulnerable dark traits with COVID-19 prevention behaviour. Highlights: Primary and secondary psychopathy predicted less COVID-19 prevention behaviour. Grandiose narcissism predicted less COVID-10 prevention behaviour. Reduced coronavirus severity predicted less COVID-19 prevention behaviour. BPD traits predict fear of COVID-19 and COVID-19 prevention behaviour. No associations were observed for vulnerable narcissism.